Corporate finance and fixed investment : an econometric study - Anderson, W. H. Locke (Boston : Division of Research, Graduate School of Business Administration, Harvard University, 1964)
This book deals with the investment and financial decisions of manufacturing corporations.. In analyzing these decisions, He has emphasized the interactions between decisions to acquire physical assets and decisions as to sources of funds and the management of liquid assets.
Including bibliographical references and index.
osa 25/01/2019
Loans
Keywords: Corporations; Saving and investment